Peningkatan Hasil Belajar Iman kepada Hari Akhir Melalui Model Cooperative Learning di Kelas V SD Negeri 13 Tanjung Beringin Kecamatan Lubuk Sikaping - Refinita, Haida (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve students’ learning outcomes on the topic of belief in the Hereafter through the application of the Cooperative Learning model in Grade V students at SD Negeri 13 Tanjung Beringin. This research uses a quantitative approach with a Classroom Action Research (CAR) design. The subjects of this study were 25 students, consisting of 13 male and 12 female students. The results of the study show a significant improvement in students’ learning outcomes, with an average score increasing from 80.4 in Cycle I to 82.8 in Cycle II. Through this model, students were more actively involved in discussions and gained a better understanding of the material about the Hereafter. This study concludes that Cooperative Learning can enhance the quality of learning and improve students’ learning outcomes in Islamic Religious Education.